No Place to Hide : a Novel - Eason, Lynette (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2015)
"It's not every day you see your childhood friend and onetime crush on national news. Jackie Sellers just wishes it were under different circumstances. She can't believe that Ian Lockwood is wanted in connection with a terrorist plot, and she's determined to find him and help him clear his name. But she's not the only one looking. The FBI wants him captured. The bad guys want him dead. Ian just wants to stay alive long enough to save thousands of innocent lives"--Amazon.com.
Keywords: Terrorism investigation -- Fiction; Terrorism -- Fiction -- Prevention; Man-woman relationships -- Fiction; Mystery fiction; Romantic suspense fiction; Christian fiction